Christology and justification in Jose de Acosta - Bertoldo, Fernando Cardoso (Vox Scripturae - Revista Teológica Internacional, 2017)
This article presents aspects of evangelization from Christology and Justification in Jose de Acosta (1540-1600), more specifically from the work De Procuranda Indorum Salut. Our author rebates for education those who considered the Indians unable to receive the Christian doctrine. Acosta then evaluates the history of the Indians with the concept of superstition and idolatry, but these concepts do not mean inability to receive the Gospel. In his thinking, indigenous customs were wicked, but they had rationality and ability to adhere to the faith. Sets up then increasingly at the thought of Acosta, the need of the proclamation of Jesus Christ to the Indians and all infidels. No one is so ignorant who does not understand or can think somehow in God and the human person, and that God became man and that man is Jesus Christ.